China and its policies with Latin America during the 20th century - Naranjo Navas, Christian Paúl (2021)
This essay analyzes the primary political and economic interests of China in Latin America, taking into account the Chinese investments in strategic sectors in Venezuela, Brazil, Argentina and Ecuador as a focal point. The essay reaches three conclusions: first, the growth of China's influence in the region was made possible by the political withdrawal of the United States; second, China's growing need to supply its raw material industries; and third, the generation of debtors that would be linked to China for many years.